When "Macbeth" Meets Chinese Opera: A Crossroad of Humanity - Xingxing, Li (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
As one of the four Shakespeare’s great tragedies, Macbeth, with its thrilling story line and profound exploration of human nature, has been adapted for plays and movies worldwide. Though Macbeth was introduced to China just before the May 4th Movement in 1919, its characters and plot have attracted the world in the past 100 years. Macbeth was firstly adapted into a folk play Theft of a Nation during the modern play period, to mock Yuan Shikai’s restoration of the monarchy, who was considered as a usurper of Qing dynasty, followed by Li Jianwu’s adaptation Wang Deming, Kun opera Bloody Hands, Taiwanese version of Beijing opera Lust and the City, Hong Kong version of Cantonese opera The Traitor, Macao version of small theater play If I were the King, Anhui opera Psycho, Shaoxing opera General Ma Long, Wu opera Bloody Sword, a monodrama of Sichuan opera Lady Macbeth, and an experimental Kun opera Lady. Therefore, this essay aims to comb the relations among various adaptations of Macbeth, to discover the advantages and disadvantages of different methodologies by examining the spiritual transformations of the main character Macbeth and reinvention of Lady Macbeth, and ultimately to observe acceptance of Chinese public, which might give thoughts to communications of overseas literature in China.